The Influence of Environmental Sound Training on the Perception of Spectrally Degraded Speech and Environmental Sounds - Shafiro, Valeriy (SAGE Publications, 2012)
Perceptual training with spectrally degraded environmental sounds results in improved environmental sound identification, with benefits shown to extend to untrained speech perception as well. The present study extended those findings to examine longer-term training effects as well as effects of mere repeated exposure to sounds over time. Participants received two pretests (1 week apart) prior to a week-long environmental sound training regimen, which was followed by two posttest sessions, separated by another week without training. Spectrally degraded stimuli, processed with a four-channel vocoder, consisted of a 160-item environmental sound test, word and sentence tests, and a battery of basic auditory abilities and cognitive tests. Results indicated significant improvements in all speech and environmental sound scores between the initial pretest and the last posttest with performance increments following both exposure and training. For environmental sounds (the stimulus class that was trained), the magnitude of positive change that accompanied training was much greater than that due to exposure alone, with improvement for untrained sounds roughly comparable to the speech benefit from exposure. Additional tests of auditory and cognitive abilities showed that speech and environmental sound performance were differentially correlated with tests of spectral and temporal-fine-structure processing, whereas working memory and executive function were correlated with speech, but not environmental sound perception. These findings indicate generalizability of environmental sound training and provide a basis for implementing environmental sound training programs for cochlear implant (CI) patients.